Modulation of Spinal GABAergic Inhibition and Mechanical Hypersensitivity following Chronic Compression of Dorsal Root Ganglion in the Rat - Moon Chul Lee; Taick Sang Nam; Se Jung Jung; Young S. Gwak; Joong Woo Leem (Neural Plasticity)
Chronic compression of dorsal root ganglion (CCD) results in neuropathic pain. We investigated the role of spinal GABA in CCD-induced pain using rats with unilateral CCD. A stereological analysis revealed that the proportion of GABA-immunoreactive neurons to total neurons at L4/5 laminae I–III on the injured side decreased in the early phase of CCD (post-CCD week 1) and then returned to the sham-control level in the late phase (post-CCD week 18). In the early phase, the rats showed an increase in both mechanical sensitivity of the hind paw and spinal WDR neuronal excitability on the injured side, and such increase was suppressed by spinally applied muscimol (GABA-A agonist, 5 nmol) and baclofen (GABA-B agonist, 25 nmol), indicating the reduced spinal GABAergic inhibition involved. In the late phase, the CCD-induced increase in mechanical sensitivity and neuronal excitability returned to pre-CCD levels, and such recovered responses were enhanced by spinally applied bicuculline (GABA-A antagonist, 15 nmol) and CGP52432 (GABA-B antagonist, 15 nmol), indicating the regained spinal GABAergic inhibition involved. In conclusion, the alteration of spinal GABAergic inhibition following CCD and leading to a gradual reduction over time of CCD-induced mechanical hypersensitivity is most likely due to changes in GABA content in spinal GABA neurons.